The Era of the Rightly Guided Caliphs (Personality of the Caliphs, Succession System, Politics, Civilization Development) - Misnahwati; Siti Rukmana; Yudha Pratama (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
This study aims to investigate and analyze key aspects of the Era of the Rightly Guided Caliphs in Islamic history, including the personality of the caliphs, the succession system, politics, and the development of civilization. The research method involves the historical analysis of relevant primary and secondary sources, along with the interpretation and synthesis of the collected data. The findings reveal that the personalities of the caliphs during the Rashidun period were marked by leadership qualities that were just, wise, and servant-hearted towards the Muslim community. Caliphs Abu Bakr, Umar ibn Khattab, Uthman ibn Affan, and Ali ibn Abi Talib were known as leaders who firmly upheld principles of justice and truth. The succession system in the Rashidun period was studied with a focus on the process of selecting a caliph, consultation mechanisms, and the factors influencing the determination of a successor. The research reveals that the succession system was based on consultation among prominent Muslim figures, considering leadership qualities, integrity, and the support of the community.